The accomplices: Heparan sulfates and N-glycans foster SARS-CoV-2 spike:ACE2 receptor binding and virus priming - Paiardi, Giulia; Ferraz, Matheus; Rusnati, Marco; Wade, Rebecca C. (Proceedings of the National Academy of Sciences of the United States of America, 2024)
Although it is well established that the SARS-CoV-2 spike glycoprotein binds to the host cell ACE2 receptor to initiate infection, far less is known about the tissue tropism and host cell susceptibility to the virus. Differential expression across different cell types of heparan sulfate (HS) proteoglycans, with variably sulfated glycosaminoglycans (GAGs), and their synergistic interactions with host and viral N-glycans may contribute to tissue tropism and host cell susceptibility. Nevertheless, their contribution remains unclear since HS and N-glycans evade experimental characterization. We, therefore, carried out microsecond-long all-atom molecular dynamics simulations, followed by random acceleration molecular dynamics simulations, of the fully glycosylated spike:ACE2 complex with and without highly sulfated GAG chains bound. By considering the model GAGs as surrogates for the highly sulfated HS expressed in lung cells, we identified key cell entry mechanisms of spike SARS-CoV-2. We find that HS promotes structural and energetic stabilization of the active conformation of the spike receptor-binding domain (RBD) and reorientation of ACE2 toward the N-terminal domain in the same spike subunit as the RBD. Spike and ACE2 N-glycans exert synergistic effects, promoting better packing, strengthening the protein:protein interaction, and prolonging the residence time of the complex. ACE2 and HS binding trigger rearrangement of the S2’ functional protease cleavage site through allosteric interdomain communication. These results thus show that HS has a multifaceted role in facilitating SARS-CoV-2 infection, and they provide a mechanistic basis for the development of GAG derivatives with anti-SARS-CoV-2 potential.